116 Matrix metalloproteinase inhibition attenuates reperfusion injury, independently of and additive to mitochondrial permeability transition pore inhibition. (16th May 2012) - Bell, R M; Hendy, Cara; Bruce-Hickman, D; Davidson, S; Breckenridge, R; Yellon, D M
Abstract : While matrix-metalloproteinase (MMP) inhibitors appear to protect against myocardial ischaemia/reperfusion injury, the mechanisms are poorly understood. We hypothesised that cardioprotection resultant from MMP inhibition is independent of mitochondrial permeability transition pore (mPTP), the end-effector of ischaemic postconditioning (iPOC). In ex-vivo and in-vivo mouse hearts, we investigated whether the MMP inhibitor, ilomostat (0.25 μmol/l), at the onset of reperfusion, could engender protection in the absence of cyclophillin-D (CyPD), an initiator of mPTP opening, against injurious ischaemia/reperfusion. We have previously demonstrated that CyPD knockout (KO) hearts have inherent resistance to ischaemia/reperfusion injury, and cannot be further protected by either pre or post conditioning regimen. Therefore to further attenuate infarction in this model would require a mechanism independent of the mPTP. We found that ilomastat attenuated infarct size in wild type (WT) animals (37%±2.8% to 22%±4.3%, equivalent to ischaemic post conditioning (iPostC—6 cycles of 10sec reperfusion/ischaemia), 27%±2.1%, p<0.05). CyPD KO hearts had smaller infarcts compared to their conditioned WT brethren (28%±4.2%) and iPostC failed to protect, indicative of a pre-protected phenotype, yet ilomastat significantly attenuated infarct size in these hearts (11%±3.0%, p<0.001). Moreover, the infarct size seen in the ilomastat treated KO hearts was significantly smaller than that seen in the ilomastat treated WT hearts (p<0.05), suggesting that mPTP and MMP inhibition is summative. Furthermore, ilomastat was found to be protective following prolonged injurious ischaemia (50 min), an injurious regimen that iPostC in WT was insufficient to protect against (49%±7.8% to 31%±2.8%, p<0.05). Interestingly, we found that delaying administration of ilomastat 15 min after the onset of reperfusion results in failure to protect the heart, indicating an effect upon early reperfusion injury, rather than post infarct remodelling. Isolated mouse WT myocytes, loaded with the potentiometric dye Tetramethyl Rhodamine Methyl Ester (TMRM) and exposed to laser light generate reactive oxygen species, a potent opener of the mPTP. The time to mPTP opening can therefore be used as an assay of drug interaction with the mPTP. Using cyclosporine as a postive control, we found that ilomastat, unlike cyclosporine, did not delay mPTP and was equivalent to the vehicle negative control, indicating no interaction with mPTP in isolated cardiomyocytes. In conclusion, we demonstrate that cardioprotection by MMP inhibition is independent of CyPD/mPTP function and can augment the protection seen following iPostC even after prolonged cardiac ischaemia. We believe that this may be through a novel molecular target not implicated in the recognised preconditioning paradigm, and one that may have potential therapeutic implications for clinical practice through attenuating acute reperfusion injury in acute coronary syndromes.